Innovation management : A study of business recovery strategy among Chinese Muslims entrepreneurs in Malaysia - Lim, Ooi Wei; Muhammad Asraf, Abdullah (2023)
Many Small Medium Enterprises (SMEs) are currently facing sustained crisis and challenges posed by the COVID-19 pandemic. To address such challenges, this paper aims to investigate multiple ways of innovation management as the business recovery strategies in which Chinese Muslims entrepreneurs employed to build resilience in the unpredictable business environment during and post COVID-19 pandemic. Data has been collected through detailed personal interviews of the five (5) small-scale businesses among local and foreign Chinese Muslims in food and beverage industry in Peninsular Malaysia. Based on qualitative research comprising of case study approach, this study reveals remarkable business resilience among the Chinese Muslim entrepreneurs in addressing the challenges faced during and after the decade of crisis (COVID-19 pandemic) that affected their business operation in Malaysia. From the various and distinctive perspectives of the Chinese Muslim entrepreneurs, this study provides insightful business recovery plans and approaches as the livelihood strategies in dealing with an unpredictable business environment. The findings of this study will enhance the SME’s resilience capability and responsiveness to achieve business sustainability in facing any crisis.